A METHODOLOGICAL APPROACH TO THE ASSESSMENT OF THE COMPONENTS OF THE INTERNATIONAL COMPETITIVENESS OF THE ELECTRIC POWER INDUSTRY IN CONDITIONS OF UNCERTAINTY - О. О. Зробок; О. А. Гавриш (Ekonomìčnij Vìsnik Nacìonalʹnogo Tehnìčnogo Unìversitetu Ukraïni "Kiïvsʹkij Polìtehnìčnij Institut", 2024)
The article is devoted to the development of a methodological approach for assessing the components of international competitiveness of the electric power industry under conditions of uncertainty. The article uses such general scientific research methods as critical, systemic and structural analysis and synthesis, decomposition, abstraction, and deduction. Research results: the essence of the international competitiveness of the electric power industry is defined, its components are structured, and a methodological approach to their assessment is developed, which takes into account the conditions of uncertainty of the factors of the international competitive environment. The practical significance of the research results is that, based on the developed methodological approach, it is possible to determine how the uncertainty of the factors of the international competitive environment affects the components of the international competitiveness of the electric power industry, and the establishment of this formal relationship will allow economic entities in the electric power industry to better predict their activities under conditions of uncertainty and identify ways to minimize it.